1986
DOI: 10.1085/jgp.88.1.107
|View full text |Cite
|
Sign up to set email alerts
|

Pressure injection of calcium both excites and adapts Limulus ventral photoreceptors.

Abstract: Single pressure injections of 1-2 mM calcium aspartate into the light-sensitive region of Limulus ventral photoreceptors resulted in a rapid, 20-40-mV depolarization lasting -2 s . The depolarization closely followed the rise in intracellular free calcium caused by the injection, as indicated by aequorin luminescence . The depolarization was followed by reversible desensitization (adaptation) of responses to both light and inositol 1,4,5 trisphosphate . Similar single injections of calcium into the light-insen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(64 citation statements)
references
References 31 publications
5
59
0
Order By: Relevance
“…While under steady state conditions free cytosolic calcium im pairs the generation of single-photon responses, some rapid (probably local) increase in Caj ap pears obligatory to evoke them. Indeed, calcium led to depolarization of the photoreceptor only when pressure-injected (Payne et al, 1986b), not when applied ionophoretically (Lisman and Brown, 1972).…”
Section: Effect O F Calcium On Response Generation and Adaptationmentioning
confidence: 98%
See 1 more Smart Citation
“…While under steady state conditions free cytosolic calcium im pairs the generation of single-photon responses, some rapid (probably local) increase in Caj ap pears obligatory to evoke them. Indeed, calcium led to depolarization of the photoreceptor only when pressure-injected (Payne et al, 1986b), not when applied ionophoretically (Lisman and Brown, 1972).…”
Section: Effect O F Calcium On Response Generation and Adaptationmentioning
confidence: 98%
“…More controversially discussed is the role of calcium ions in the excitation process. Injection of M. D orlöchter et al ■ Calcium -Independent Photoresponse in Lim ulus Ventral Photoreceptor 447 calcium into ventral photoreceptors increased the light response in calcium-deprived cells, or elicited inward currents similar to those caused by light so that an obligatory role for calcium in excitation was proposed (Bolsover and Brown, 1985;Payne, Corson and Fein, 1986b;Shin, Richard and Lisman, 1993). On the other hand, application of calcium buffer or agents blocking calcium release did not completely inhibit the photocurrent indi cating calcium-independent initiation of a light re sponse (Frank and Fein, 1991;Contzen, Richter and Nagy, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Third, although PKC inhibitors slightly sensitize the photoresponse and antagonize the effect of PKC activators, they do not reverse the decrease in sensitivity associated with light adaptation for the adaptation protocols that we describe. Finally, injection of calcium ions alone into the photoreceptor can f ully mimic light adaptation (Brown and Lisman, 1975;Fein and Charlton, 1977) and suppress the response to InsP 3 (Payne et al, 1986a) without any requirement for the addition of DAG or a surrogate. However, each of these results is subject to caveats, and it is not possible to conclude from these results that PKC plays no role in adaptation.…”
Section: Pkc Activators Do Not Mimic Light Adaptation Nor Do Pkc Inhmentioning
confidence: 99%
“…Robinson, Wood, Szuts, Fein, Hamm & Lisman (1990) recently reported that three different light-activated G-proteins exist in squid photoreceptors. Payne et al (1986a) have shown that calcium injection induces a membrane current in Limulus ventral nerve photoreceptor similar to that induced by light. Buffering the intracellular calcium does not completely block the light-induced response, although it blocks the calcium-induced response.…”
Section: Introductionmentioning
confidence: 95%